Simulation study of heat energy potential of asphalt solar collectors. (May 2014) - Wu, S. P.; Li, B.; Pan, P.; Guo, F.
Abstract : Using black asphalt pavements as solar collectors is an emerging technology for snow-melting of pavements in winter or cooling and heating of adjacent buildings. The primarily concerned issues of this technology are the heat energy potential and its critical parameters. In this paper, a transient, two-dimensional finite element model is developed to investigate the heat transfer process in both neat and conductive asphalt pavements. The results from thermal properties tests show that thermal conductivity of asphalt mixtures may increase by more than 30% due to the addition of conductive fillers. Besides, the modelling results indicate that the higher thermal conductivity may result in acceleration of the heat conduction and increase in temperature at deeper depths in asphalt pavements. According to the calculated results of heat energy potential based upon the model, the energy derived from a neat asphalt collector or a conductive one is considerable. Thermal properties of asphalt materials have no significant impact on energy absorption in asphalt pavements.